Detecting neuropsychiatric fluctuations in Parkinson’s Disease using patients’ own words: the potential of large language models - Matilde Castelli; Mario Sousa; Illner Vojtech; Michael Single; Deborah Amstutz; Marie Elise Maradan-Gachet; Andreia D. Magalhães; Ines Debove; Jan Rusz; Pablo Martinez-Martin; Raphael Sznitman; Paul Krack; et al. (npj Parkinson's Disease)
Abstract Over the past decade, neuropsychiatric fluctuations in Parkinson’s disease (PD) have been increasingly recognized for their impact on patients’ quality of life. Speech, a complex function carrying motor, emotional, and cognitive information, offers potential insights into these fluctuations. While previous studies have focused on acoustic analysis to assess motor speech disorders reliably, the potential of linguistic patterns associated with neuropsychiatric fluctuations in PD remains unexplored. This study analyzed the content of spontaneous speech from 33 PD patients in ON and OFF medication states, using machine learning and large language models (LLMs) to predict medication states and a neuropsychiatric state score. The top-performing model, the LLM Gemma-2 (9B), achieved 98% accuracy in differentiating ON and OFF states and its predicted scores were highly correlated with actual scores (Spearman’s ρ = 0.81). These methods could provide a more comprehensive assessment of PD treatment effects, allowing remote neuropsychiatric symptom monitoring via mobile devices.